Let's Take a Field Trip to an Ant Colony - Furgang, Kathy (New York The Rosen Publishing Group,Inc, 2000)
An introduction to ant society, discussing roles and duties of individual ants, the creation of a nest, the anatomy of an ant, and the relationship of these insects to humans.
Keywords: Ants; Insect societies; Series: Neighborhoods in nature